Arctic stratospheric dehydration – Part 1: Unprecedented observation of vertical redistribution of water - S. M. Khaykin; I. Engel; H. Vömel; I. M. Formanyuk; R. Kivi; L. I. Korshunov; M. Krämer; A. D. Lykov; S. Meier; T. Naebert; M. C. Pitts; M. L. Santee; et al. (Atmospheric Chemistry and Physics, 2013)
We present high-resolution measurements of water vapour, aerosols and clouds in the Arctic stratosphere in January and February 2010 carried out by in situ instrumentation on balloon sondes and high-altitude aircraft combined with satellite observations. The measurements provide unparalleled evidence of dehydration and rehydration due to gravitational settling of ice particles. An extreme cooling of the Arctic stratospheric vortex during the second half of January 2010 resulted in a rare synoptic-scale outbreak of ice polar stratospheric clouds (PSCs) remotely detected by the lidar aboard the CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation) satellite. The widespread occurrence of ice clouds was followed by sedimentation and consequent sublimation of ice particles, leading to vertical redistribution of water inside the vortex. A sequence of balloon and aircraft soundings with chilled mirror and Lyman- α hygrometers (Cryogenic Frostpoint Hygrometer, CFH; Fast In Situ Stratospheric Hygrometer, FISH; Fluorescent Airborne Stratospheric Hygrometer, FLASH) and backscatter sondes (Compact Optical Backscatter Aerosol Detector, COBALD) conducted in January 2010 within the LAPBIAT (Lapland Atmosphere-Biosphere Facility) and RECONCILE (Reconciliation of Essential Process Parameters for an Enhanced Predictability of Arctic Stratospheric Ozone Loss and its Climate Interactions) campaigns captured various phases of this phenomenon: ice formation, irreversible dehydration and rehydration. Consistent observations of water vapour by these independent measurement techniques show clear signatures of irreversible dehydration of the vortex air by up to 1.6 ppmv in the 20–24 km altitude range and rehydration by up to 0.9 ppmv in a 1 km thick layer below. Comparison with space-borne Aura MLS (Microwave Limb Sounder) water vapour observations allow the spatiotemporal evolution of dehydrated air masses within the Arctic vortex to be derived and upscaled.